034 Updated safety analysis of ocrelizumab in multiple sclerosis. Issue 6 (27th May 2022) - Schmierer, Klaus; Hauser, Stephen L; Kappos, Ludwig; Montalban, Xavier; Craveiro, Licinio; Hughes, Richard; Prajapati, Kalpesh; Koendgen, Harold; Pradhan, Ashish; Wolinsky, Jerry S
Abstract : Background: Ongoing safety reporting is crucial to understanding the long-term benefit-risk profile of ocrelizumab in multiple sclerosis (MS). Safety/efficacy of ocrelizumab have been characterised in Phase II (NCT00676715 ) and III (NCT01247324 /NCT01412333/NCT01194570 ) trials in relapsing-remitting MS, relapsing MS (RMS) and primary progressive MS (PPMS). Here, we report safety evaluations from ocrelizumab clinical trials and open-label extensions up to January 2019, and selected post-marketing data. Methods: Safety outcomes are reported for the ocrelizumab all-exposure population in Phase II/III and ongoing Phase IIIb trials. To account for different exposure lengths, rates per 100 patient years (PY) are presented. Results: In clinical trials, 4, 611 patients with MS received ocrelizumab (14, 329 PY exposure). Reported rates per 100 PY (95% confidence interval) were: adverse events (AEs), 252 (249–254); serious AEs, 7.33 (6.89–7.79); infections, 76.7 (75.3–78.2); serious infections, 1.99 (1.77–2.23); malignancies, 0.46 (0.35–0.58); and AEs leading to discontinuation, 1.08 (0.92–1.27). Updated ocrelizumab all-exposure population data and selected post-marketing data will be presented. Conclusions: Reported event rates in the ocrelizumab all-exposure clinical trial population and post-mar- keting settings remain generally consistent with the controlled treatment period in RMS/PPMS populations. Regular reporting of long-term safety data will continue. k.schmierer@qmul.ac.uk